2020
DOI: 10.14738/assrj.73.7993
|View full text |Cite
|
Sign up to set email alerts
|

Research Methods and Methodology

Abstract: Research is an interesting field of study which every student or scholar has to encounter in the course of time. The objective of this paper is to explore the various approaches to research so that students can gain insight and understanding. This paper attempts a review of the various approaches to research so that the reader can make an informed choice. The paper is based on secondary sources plus the author's own experience borne from decades of teaching. This paper does not claim to have exhausted the list… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…This study focuses on causal relationships where micro-business variables and mustahiq welfare variables are influenced by productive zakat variables. This research is a combination of descriptive research and problem solving (descriptive and problem sloving research) which is a study that seeks to determine, identify or describe what will happen, then to solve specific problems in order to make specific decisions or conclusions as well (Díaz-Reza, García-Alcaraz, & Martínez-Loya, 2019;Nassaji, 2015;Sakyi, Musona, & Mweshi, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…This study focuses on causal relationships where micro-business variables and mustahiq welfare variables are influenced by productive zakat variables. This research is a combination of descriptive research and problem solving (descriptive and problem sloving research) which is a study that seeks to determine, identify or describe what will happen, then to solve specific problems in order to make specific decisions or conclusions as well (Díaz-Reza, García-Alcaraz, & Martínez-Loya, 2019;Nassaji, 2015;Sakyi, Musona, & Mweshi, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, convenience sampling was designed for the target population; since, the researcher worked with these groups of students (Sakyi et al, 2020). The study followed the next steps shown in the figure 1.…”
Section: Research Methods Techniques and Instrumentsmentioning
confidence: 99%
“…Bu tür araştırmaların çoğunda nitel veri toplama araçlarının kullanıldığı görülmektedir (Stebbins, 2011). İlgili konuda gelecekte daha derinlemesine araştırmalar yapmak ve buna teorik zemin oluşturmak için keşfedici araştırmalar gerçekleştirilmektedir (Sakyi, Musona ve Mweshi, 2020). Bu tür araştırmalar, araştırma konusu ile ilgili literatür taraması ile başlamaktadır.…”
Section: Araştırma Türüunclassified